Estudo cinético da produção de ácido clavulânico e cefamicina C por Streptomyces clavuligerus - Oliveira, Liliane Maciel de (Universidade Federal de São Carlos, 2009)
Clavulanic acid and cephamycin C are ϐ-lactam compounds, an important group of drugs used in the treatment of several bacterial diseases, and are simultaneously produced by the bacteria Streptomyces clavuligerus. Similarly to any secondary metabolite, the production of these compounds can be controlled by the intracellular concentration of precursors and cofactors, and their availability to be used in the secondary metabolism depends directly on the nutritional composition changes in the culture media. Based on these facts, the aim of this work was to evaluate the effect of some carbon and nitrogen sources on clavulanic acid (CA) and cephamycin C (CefC) production by S. clavuligerus, and to propose a kinetic model able to represent the influence of these compounds on the behavior of this bioprocess. The fermentation runs were carried out in shakers, using synthetic media, combining glycerol, maltose, asparagine, proline, glutamic acid and ornithine. The results showed that both carbon and nitrogen sources were limitants. The fermentations with media containing maltose gave the highest CA and CefC productions, but the bacterial growth was lower. On the other hand, the fermentations with the media containing glycerol gave a higher bacterial growth and lower production, except for the fermentation using the media composed by glycerol, proline and ornithine, that gave the lowest growth and CA production, and there was no CefC production. The aditition of glutamic acid in the medium containing maltose and asparagine, and the aditition of more asparagine in this same medium favored the bacterial growth, but have no effect on production. The glutamic acid effect on the growth was more intense than that of asparagine. Based on the obtained results, a kinetic model describing the growth, CA and CefC production was proposed. The adjustment of the model to the experimental data was made in six different fermentations. The model had a good adjustment to four of all the media tested, and was able to represent the bioprocess within the conditions studied in this work.
Keywords: Fermentação; Ácido clavulânico; Cefamicina C; Modelagem matemática; ENGENHARIAS::ENGENHARIA QUIMICA